Experimental analysis of the unsteady flow inside a Wells turbine - Licheri Fabio (EDP Sciences, 2021)
One of the most promising technologies for sea-wave energy conversion is the one based on the Oscillating Water Column (OWC) principle. The system is composed of two units, an open chamber that converts the sea water motion into an alternating air-flow, and a turbine driven by the latter. The alternating flow of air requires a turbine capable of maintaining the same direction of rotation. The Wells turbine represents the simplest and most reliable device for this purpose. It is a self-rectifying axial turbine characterized by a rotor with symmetric blades staggered at 90 degrees relative to the axis of rotation. The vast majority of experimental works on Wells turbines and OWC devices analyzed their performance from a global point of view, often under steady conditions, in order to evaluate the pressure drop through the rotor, the torque produced and thus the turbine efficiency. This paper presents an experimental analysis of the three-dimensional flow inside a Wells turbine which operates in a facility capable of reproducing the alternating air-flow typical of an OWC system. The investigation is based on local flow measurements using several probes in order to describe the non-stationary air-flow, both up- and down-stream of the rotor at different heights, along the span of the blade. The investigation, conducted on a high-solidity turbine, details the behavior of the flow field inside the machine, aiming to provide a detailed description that can guide the aerodynamic optimization of the entire system (chamber and turbine) for a better energy conversion.